2022
DOI: 10.3390/jmmp7010007
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strength and Microstructure of Rotary Friction-Welded Carbon Steel and Stainless Steel Joints

Abstract: Due to the different properties of the materials, the fusion welding of dissimilar metals may be difficult. Structural irregularities may form as a result of various phase transformations during welding. Solid-state welding, as opposed to fusion welding, occurs below the melting temperature. As a result of the melting and solidification phenomena that happen in fusion welding, solid-state welding is expected to reduce the potential for phase transformation. This paper describes the use of a rotary friction wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The main challenge during these RFW tests was to control the thermomechanical processing, due to the very complex nature of the chemical composition of the advanced steels, considered in this work as highly alloyed steels, which, in addition to the obvious thermophysical differences, such as the melting point, may cause brittle components in the joint. Therefore, due to the intense thermomechanical treatment that the material undergoes, combined with the operating conditions of the RFW process, microstructural phenomena, such as dynamic recrystallization and grain refinement, solidstate phase transformations, deformation-induced precipitation, solid dissolution, and grain growth, can occur [16]. Consequently, the formation of the microstructure of the metallic joint and the corresponding mechanical resistance can be influenced (positively or not) by all of these metallurgical phenomena.…”
Section: Microstructure Of the Welded Steelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main challenge during these RFW tests was to control the thermomechanical processing, due to the very complex nature of the chemical composition of the advanced steels, considered in this work as highly alloyed steels, which, in addition to the obvious thermophysical differences, such as the melting point, may cause brittle components in the joint. Therefore, due to the intense thermomechanical treatment that the material undergoes, combined with the operating conditions of the RFW process, microstructural phenomena, such as dynamic recrystallization and grain refinement, solidstate phase transformations, deformation-induced precipitation, solid dissolution, and grain growth, can occur [16]. Consequently, the formation of the microstructure of the metallic joint and the corresponding mechanical resistance can be influenced (positively or not) by all of these metallurgical phenomena.…”
Section: Microstructure Of the Welded Steelsmentioning
confidence: 99%
“…Materials 2024, 17, x FOR PEER REVIEW 10 of 18 solid-state phase transformations, deformation-induced precipitation, solid dissolution, and grain growth, can occur [16]. Consequently, the formation of the microstructure of the metallic joint and the corresponding mechanical resistance can be influenced (positively or not) by all of these metallurgical phenomena.…”
Section: Microstructure Of the Welded Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the higher hardness was observed at the weld interface of the Inconel 718/2.5Cr-1Mo (F22) steel RFWed joints compared with the RFWed joints with an Inconel 625 interlayer. Firmanto et al [ 35 ] used the RFW technique to investigate the characteristics of 304 stainless steel and low-carbon steel joints. Three factors, namely friction time, friction pressure, and upset pressure, had a significant influence on the tensile strength.…”
Section: Introductionmentioning
confidence: 99%